Pengaruh Pemberian Konseling Gizi Terhadap Peningkatan Pengetahuan Dan Konsumsi Zat Gizi Ibu Hamil Anemia Di Wilayah Kerja Puskesmas Pejeruk, Ampenan, Kota Mataram - Si Luh Putu Febriana Putri; Lalu Khairul Abdi; Niketut Sri Sulendri; Susilo Wirawan (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. One problem that is often encountered in pregnancy which is one of the factors in the high maternal mortality rate in Indonesia is anemia. Based on data from the Mataram City Health Office, it is known that the prevalence of anemic pregnant women has increased in September 2016 the prevalence of anemic pregnant women is 6.11%. Pejeruk Health Center which shows the highest prevalence of anemia in pregnant women in the city of Mataram by 27.08%. Research Methods. The research design used was Quasi Experimental with research design, namely Non Equivalent Control Group (Pretest and Posttest) with a study sample of 21 pregnant women who had anemia in the second trimester. How to take samples in this study by using Total Samples. The data analysis used was the Independent T-test to see the differences from the 2 groups, and to see the effect of nutritional counseling on knowledge and consumption using a statistical test in the form of a Paired T-Test with (p = <0.05). Research Result. The results showed that there was an effect of providing nutritional counseling on increasing knowledge and consumption of nutrients, namely Energy and Protein p = <0.005) and there was no effect of increasing iron (Fe) consumption (p => 0.005) Conclusion. The influence of giving nutritional counseling on increasing the knowledge and consumption of nutrients for anemia pregnant women in the pujeruk health center area